2022
DOI: 10.1002/hec.4498
|View full text |Cite
|
Sign up to set email alerts
|

Rainfall shocks, child mortality, and water infrastructure

Abstract: I study the effect of rainfall shocks on child mortality at a sub‐national level for a global set of developing countries. I establish that negative (positive) shocks to rainfall lead to an increase (drop) in child deaths overall. Low‐income countries (LICs) and the group of countries reliant on agriculture are affected the most due to negative rainfall shocks. In LICs, the impact of negative rainfall shocks is mitigated by around 60% in districts located downstream to dams, an effect predominant among less af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 81 publications
(124 reference statements)
0
3
0
Order By: Relevance
“…The sensitivity of changes in health or poverty to income is found to be a decreasing function of income inequality (Biggs et al., 2010; Fosu, 2010). In a recent study, Ponnusamy (2022) has shown that the effects of droughts on under‐five mortality tend to be higher in regions with higher income inequality, especially in low‐income group of countries. On the other hand, the studies that focus on the relationship between ethnic inequality and societal or developmental outcomes are limited, with the majority of studies focused on ethnic heterogeneity.…”
Section: Literaturementioning
confidence: 99%
“…The sensitivity of changes in health or poverty to income is found to be a decreasing function of income inequality (Biggs et al., 2010; Fosu, 2010). In a recent study, Ponnusamy (2022) has shown that the effects of droughts on under‐five mortality tend to be higher in regions with higher income inequality, especially in low‐income group of countries. On the other hand, the studies that focus on the relationship between ethnic inequality and societal or developmental outcomes are limited, with the majority of studies focused on ethnic heterogeneity.…”
Section: Literaturementioning
confidence: 99%
“…The factors linking drought with increased health risks operate within the context of existing infrastructure and health service provision. Several studies have investigated mortalitymitigating channels, including exploiting quasi-experimental evidence on trade openness 4 , credit and liquidity access 5,6 , and water and sanitation infrastructure [7][8][9] . Yet, randomized controlled trial-based estimates of effective adaptation policies are missing 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Child mortality rates are affected by all of these factors taken together. Low rainfall and drought can reduce the availability of clean water, which can raise the risk of waterborne diseases, while high temperatures can cause heat-related ailments [ 21 , 22 ]. Children's respiratory health is negatively impacted by rising CO 2 emissions, which contribute to air pollution [ 23 ].…”
Section: Introductionmentioning
confidence: 99%